Outdoors Activity as A Protective Factor of Myopia Incidence in Children - Widya Anandita; Julie D. Barliana (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Outdoors activities emerge as one of protective factors in myopia incidence and progression. The aim of this literature review is to evaluate the effect of outdoor activity on preventionof myopia incidence in children age 0 to 18 years old.Methods: The literature search was conducted from MEDLINE database using Pubmed for journalarticles that were published and related to the association between outdoor activity and incidence ofmyopia, guided by MOOSE checklist. Random effect meta-analysis is done on 1 hour/week outdooractivity and incidence of myopia.Results: Thirteen studies were reviewed, 8 of which are cross-sectional studies and 5 of which arecohort studies. Random effect meta-analysis showed OR of 0.9 (CI 95% 0.59-1.55).Conclusion: Outdoor activity as protective factor in preventing incidence of myopia is still inconclusive.However, throughout most articles reviewed in this literature, there is a trend towards its protectiveeffect in preventing myopia incidence.